PENGARUH LINGKUNGAN KERJA, INSENTIF FINANSIAL DAN INSENTIF NON FINANSIAL TERHADAP KEPUASAN KERJA PADA DINAS PETERNAKAN DAN PERIKANAN KABUPATEN BOJONEGORO - jurnalmap map; Anita Setyarini Widya; Mei Indrawati; Hidayat ÔÇì (MAP (Jurnal Manajemen dan Administrasi Publik), 2018)
ABSTRACT The purpose of this study is to know the work environment, incentives finacial, non financial incentives simultaneously or partially to the employee job satisfaction, knowing the dominant variables affecting employee satisfaction as well as to know the conditions work environment, financial incentives, non financial incentives and job satisfaction employees from Departement of Animal Husbandry and Fisheries. In this research, the data collected comes from the sample data so that the data studied is the data from the sample. The method used is the survey method with the aim to find the relationship and influence between the free variable with dependent variable, and describe the variables- variables studied. The population in this study is all employees that exist in Departement of Animal Husbandry and Fisheries Bojonegoro. Sampling technique using census technique that is from whole population taken as sample, leader and researcher not included in sample. The results of this research are simultaneous work environment, financial incentives, non financial incentives have a significant effect on job satisfaction. Partially work environment, financial incentives and non financial Incentives have an effect on the significance of job satisfaction. Among the working environment, financial incentives and non-financial incentives, non-financial incentives have a dominant influence on employee job satisfaction. Keywords: work environment, financial incentives, non financial incentives, job satisfaction